2021
DOI: 10.1111/clr.13841
|View full text |Cite
|
Sign up to set email alerts
|

Vertical and horizontal ridge augmentation using customized CAD/CAM titanium mesh with versus without resorbable membranes. A randomized clinical trial

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(91 citation statements)
references
References 67 publications
(74 reference statements)
4
82
0
Order By: Relevance
“…No covering of the augmented sites with a collagen membrane or platelet‐rich plasma (PRP) or platelet‐rich‐fibrin (PRF) was adopted in this trial since their usefulness was not demonstrated yet. (Cucchi et al, 2021; Torres et al, 2010). Two cases consisted of completely edentulous maxillary atrophies, with a period of 2 weeks of postoperative healing before wearing a relined denture for esthetic purposes only.…”
Section: Discussionmentioning
confidence: 99%
“…No covering of the augmented sites with a collagen membrane or platelet‐rich plasma (PRP) or platelet‐rich‐fibrin (PRF) was adopted in this trial since their usefulness was not demonstrated yet. (Cucchi et al, 2021; Torres et al, 2010). Two cases consisted of completely edentulous maxillary atrophies, with a period of 2 weeks of postoperative healing before wearing a relined denture for esthetic purposes only.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in Figure 5 , the H: titanium-reinforced d-PTFE (80.9%) has the best effect and F: TM + CM (20.6%) has the worst effect. Since the e-PTFE membrane has good biocompatibility and can protect against blood clots, it is regarded as the gold standard barrier functional material in clinical practice [ 13 , 14 ]. Additionally, the blue dots corresponding to the B group (e-PTFE) and C group (CCM) appear to overlap.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies described membrane exposure, and both showed that the membrane exposure rate of the TM + CCM group was lower than that of the TM group [ 14 , 32 ].…”
Section: Complication Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the first 6 months after tooth extraction, horizontal bone loss of 3.96 mm and horizontal bone loss of 1.24 mm can be observed on average [ 2 ]. In order to regain sufficient bone volume, the following augmentation techniques can be used: bone blocks (autologous or allogeneic) [ 3 , 4 ] interposition bone grafting techniques such as vertical splitting [ 5 ], horizontal sandwich technique or a Le-Fort-I osteotomy [ 6 ], guided bone regeneration with titanium meshes [ 7 ], or sinus floor elevations [ 8 ]. Other less invasive treatment options include the use of zygomatic implants [ 9 ], tilted implants, or short implants [ 10 ].…”
Section: Introductionmentioning
confidence: 99%